One of the oldest Syriac monasteries: Mor Ahron - Sen, Korkmaz; Yilmaz, Sinan (Springernature, 2026)
With the emergence of Christianity, many communities across the Wider Middle East and Anatolia started to adopt the new religion. One of these communities was the Syriacs, who, although originating from modern-day Mesopotamia, reached their peak cultural development in Anatolia, where they inhabited lands across what forms the modern-day provinces of Siirt, Hakkari, Bitlis, Diyarbak & imath;r, Elaz & imath;& gbreve; and Mardin. Like every society, they continued their traditions wherever they went and architecture was no exception. As such, they introduced significant innovations in secular and religious architecture to the places they moved to and Elaz & imath;& gbreve;. This city which once housed a significant Syriac Christian community, still retains a significant number of buildings exhibiting architectural influences that can be traced back to traditional Syriac architecture. One of the most important examples of such structures in the region is the Mor Ahron Monastery. Despite its significance, this monastery has remained largely overlooked, with only one scholar (Thierry) having undertaken a piece of substantive research. The present study seeks to shed further light on the monastery. Within its scope, comprehensive investigations were carried out to assess the accuracy of previous datings of the building, to identify its users and the periods of their occupation, and to examine the contexts in which it is attested in archival documents. Additional issues addressed include the attacks directed against the monastery at various stages of its history, its present architectural condition, and the architectural modifications introduced during different phases of its existence. This work also used comparative data from other architectural examples of the era the monastery was built in and also contains photos and drawings made during the field trip performed in the process of working on this article.